Socrates - Guthrie, W. K. C. (William Keith Chambers), 1906-1981 (Cambridge : Cambridge University Press, 1971)
The third volume of Professor Guthrie's great history of Greek thought, entitled The Fifth-Century Enlightenment, deals in two parts with the Sophists and Socrates, the key figures in the dramatic and fundamental shift of philosophical interest from the physical universe to man. Each of the two parts is available as a paperback with the text, bibliography and indexes amended where necessary so that each part is self-contained. Socrates dominated the controversies of this period, as he has dominated the subsequent history of western philosophy. He was the first to identify and grapple with some of the most intractable and persistent logical and philosophical problems; but he was also and has remained a highly controversial figure because of his extraordinary personal qualities and his remarkable career. Professor Guthrie offers a balanced and comprehensive picture of the man, his life, and his thought.
I. Problem and sources. General -- Xenophon -- Plato -- Aristotle -- Comedy -- II. Life and character. Life -- Appearance and general character -- Attitude to sex and love -- Effect on others -- The divine sign: Socrates and the irrational -- Socrates and the Delphic response -- His service to the god -- Political views -- III. Philosophical significance. Philosophia de caelo devocata -- Induction and definition -- Relevance of induction and definition to Socrate's ethical aims -- The nature of Socratic definition -- The ignorance of Socrates -- Virtue is knowledge -- All wrongdoing is involuntary: Socrates a determinist? -- The good and the useful -- Self-knowledge and'care of the soul' -- Religious beliefs of Socrates: is the soul immortal? -- The legacy of Socrates -- The immediate followers of Socrates (Aristippus and Euclides).
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Socrates